Impact of acculturation on depression, perceived stress and self-esteem in young Middle Eastern American adults. (19th May 2018) - Wilson, Meredith; Thayer, Zaneta
Abstract: Background: Human biologists have a longstanding interest in understanding the biological and health impacts of migration. Acculturation, the cultural adjustment that a group or individual experiences when previously separate cultures interact, has been found to be one pathway through which migration may impact human biology and health, not only for the migrants themselves, but also their descendants. Aim: The authors conducted a pilot study to examine the relationship between acculturation and perceived stress, self-esteem and depression among young Middle-Eastern American adults. Subject and methods: Survey data were collected from 48 young Middle-Eastern American adults. Participants were divided into one of two acculturation categories, integrated (American and Middle Eastern culture oriented) and assimilated (American culture oriented). Health measures were compared between these acculturation categories. Results: Integrated individuals had significantly lower stress ( F = 8.1, p < 0.01) and depression ( F = 10.8, p < 0.01) than assimilated individuals. Integrated individuals had lower self-esteem than assimilated individuals ( F = 5.0, p < 0.05). Generational status, a proxy used for acculturation, was only significantly associated with self-esteem ( F = 3.15, p = 0.05). Conclusion: This pilot study furthers understanding of the effects acculturation can have on perceived stress and mental health among young Middle-Eastern Americans. Future research should incorporate biological measures of stress to determine the physiological impacts of acculturation.